Efforts To Improve Understanding of Islamic Religious Education Using Project Based Learning Method at MTs Al Washliyah 48 Binjai Pepper Garden - Tanjung, Risna Aini; Satriyadi, Satriyadi (Jurnal Riset Ilmu Pendidikan, 2025)
Project Based Learning (Project Based Learning) is a learning model that uses projects or activities as media. In project-based learning, students are involved in real projects that are relevant to Islamic learning material, especially fiqh material. This increases students' understanding of learning, and allows them to apply Islamic religious knowledge in daily life. Project-based learning can improve students' social skills, such as cooperation in groups, communication, and problem solving. Teachers as facilitators give assignments to students to develop their potential. Apart from that, students also develop a deeper understanding of Islamic religious values through direct experience in the projects they work on in teaching and learning activities. This research methodology uses a qualitative approach, collecting data through observation, interviews and document study, qualitative data analysis, as well as interpretation and presentation of findings. The results of the research show that the Project Based Learning model contributes to increasing students' understanding of the concept of Islamic religious education, especially in fiqh material at MTs Al Washliyah Kebun Lada Binjai.